The complete plays of Aeschylus - Aeschylus (Allen & Unwin, 1952)
Contents: The suppliant women. The Persians. The seven against Thebes. Prometheus bound. The Oresteia. The Agamemnon. The Choëphoroe. The Eumenides
Keywords: Aeschylus; Mythology; Greek